PENERAPAN IPTEKS SISTEM PENDAFTARAN TANAH BERDASARKAN UNDANG-UNDANG POKOK AGRARIA DAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 PADA KAMPUNG ASEI BESAR - James Yoseph Palenewen; Daniel Tanati; Marthinus Solossa (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This service was carried out under the title Application of IPTEKS of the Land Registration System based on the Basic Agrarian Law and Government Regulation Number 24 of 1997 in Asei Besar Village, East Sentani District, Jayapura Regency, which was carried out to partners due to a case from partners regarding misunderstanding regarding land registration and methods or procedures for land registration so that with the expertise possessed by servants, they can carry out the application of the science and technology. The method of implementing this service is carried out by applying science and technology through lectures and discussions which will be held on Saturday 31 July 2021 which will be held at the village hall as well as assistance to partners which has been carried out until now, this activity begins with preparation and coordination, then presents material about the system land registration based on statutory regulations to obtain legal certainty. The output of this service is the increase in partners' knowledge regarding land registration and land registration procedures in order to obtain guarantees of legal certainty, as well as the completeness of land registration as pre-adjudication with the aim of making it easier for partners to complete land registration.